The Harmonious Organ of Sedulius Scottus Introduction to His Collectaneum in Apostolum and Translation of Its Prologue and Commentaries on Galatians and Ephesians - Sloan, Michael C. (Millennium-Studien / Millennium Studies, 2012)
This book introduces and translates Sedulius Scottus` Prologue to his Collectaneum in Apostolum and his commentaries on Galatians and Ephesians. The introduction outlines the historical context of composition, identifies Sedulius` literary model - Servius, explains pertinent philological and stylistic issues of Sedulius` Latin, explores his use of exegetical and theological sources - predominantly Jerome, Augustine, and Pelagius. In tracing the reception of Jerome, Augustine, and Pelagius, Sedulius reveals himself as an erudite theologian as he harmonizes these three men`s sometimes discordant voices.